Stonehenge
The optical corrections can be seen on the upright and lintel of the trilithon to the left, which also has a number of axes carved on one of its uprights. These axes are of a bronze type found in the shaft graves of Mycenae; they are also similar to those made in Ireland at about the same time. These carvings and the dressing of the stones themselves were carried out by pecking with hand-held stones to chip away the surface. Rippled tooling can be seen on the uprights to the right.